Effect of Clostridium butyricum Supplementation on in vitro Rumen Fermentation and Microbiota With High Grain Substrate Varying With Media pH Levels - Jiao, Peixin; Wang, Ziwei; Wang, Xin; Zuo, Yanan; Yang, Yuqing; Hu, Guanghui; Lu, Changming; Xie, Xiaolai; Wang, Li; Yang, Wenzhu (Frontiers in Microbiology, 2022)
Clostridium butyricum (C. butyricum) can survive in low pH, and was recently suggested that the improved ruminal fermentation with supplementing C. butyricum is associated with increasing the abundance of rumen microbiota in cattle. The objective of this study was to determine the effects of increasing the doses of C. butyricum on gas production (GP) kinetics, dry matter disappearance (DMD), fermentation characteristics and rumen microbiota using a high grain substrate in batch culture varying with media pH levels. The doses of C. butyricum were supplemented at 0 (control), 0.5×106, 1×106, and 2×106 CFU/bottle, respectively, at media pH 6.0 or pH 6.6. The fermentation microbiota at 0 and 1×106 CFU/bottle were determined using the 16S rRNA high throughput sequencing technology. Overall, the GP, DMD, volatile fatty acid (VFA) concentration and ratio of acetate:propionate were higher (P<0.01) at media pH 6.6 than pH 6.0. However, there was interaction between pH × dose of C. butyricum for rate constant of GP (P=0.01), average GP rate (P=0.07) and volume of GP (P=0.06); with increasing C. butyricum supplementation, the GP kinetics were not changed at pH 6.0, but they quadratically changed at pH 6.6. Proportions of propionate (P<0.09) and butyrate (P<0.06), and NH3-N concentration (P=0.02) quadratically changed with increasing C. butyricum supplementation regardless of media pH levels. Alpha diversity indexes of Shannon and Evenness were interacted (P=0.04) between pH level and C. butyricum dose. The alpha diversity indexes increased (P<0.05) except for Chao1 with supplementation of C. butyricum. The unweighted uniFrac analysis showed that the group of control at media pH 6.0 and control at media pH 6.6, and C. butyricum and control at media pH 6.0 clustered separately from each other. At phylum level, relative abundance (RA) of Bacteroidota was lower (P<0.01) and Firmicutes was higher (P<0.01) at media pH 6.6 than pH 6.0. Moreover, RA of Proteobacteria decreased (P<0.05) with supplemented C. butyricum at both media pH levels. It concludes that media pH level and supplementation of C. butyricum effectively modulated in vitro rumen fermentation characteristics and microbiota but in a dose depending manner of C. butyricum addition.